MOTIVATIONAL ASPECT IN PERSONNEL MANAGEMENT OF AGRICULTURAL ENTERPRISES - LESHCHENKO, Zynoviia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Today, personnel are the basis of resource potential, and the enterprise’s results largely depend on how effectively they are used. The article presents the results of research on the motivational aspect of personnel management in agricultural enterprises in modern conditions. The research has unequivocally demonstrated that motivation in personnel management of agricultural enterprises is a pivotal factor. It significantly impacts labor productivity, employee satisfaction, and the overall success of the enterprise. Motivation is the key to overcoming difficulties and swiftly responding to new challenges related to climate change, globalization of markets, staff turnover, etc. The main stages of forming the labor motivation system in agricultural enterprises are outlined: determination of motivational goals and objectives, development of motivational tools, consideration of the specifics of the agricultural sector, individual approach, and monitoring and evaluation of the effectiveness of the motivational system. The main types of labor motivation in personnel management of agricultural enterprises are singled out - material motivation, non-material motivation, collective motivation, social support, and flexibility in management. The specifics of staff motivation in agricultural enterprises, which are determined by the specifics of work in agriculture (seasonality of work, its difficulty, and monotony, the influence of natural and climatic conditions, local living conditions, collective work and traditions, problems of staff turnover and their aging) are substantiated. The research findings underscore the need for a comprehensive approach to staff motivation in agricultural enterprises. This approach should take into account the specific working conditions and create a favorable environment for employees. The key to successful motivation lies in flexibility, adaptation of motivational programs to the realities of the agricultural sector and ensuring a balance between material and non-material incentives.